The effects of a smartphone game training intervention on executive functions in youth soccer players: a randomized controlled study - Heilmann, Florian; Formenti, Damiano; Trecroci, Athos; Lautenbach, Franziska (Frontiers in Sports and Active Living, 2023)
Cognitive training primarily aims to improve executive functions (EFs). It has become a popular research topic, as previous studies have provided preliminary evidence that EFs relate to sports performance. However, whether a domain-generic cognitive training intervention can improve EFs in high-performance athletes is still unclear. The present randomized controlled study aimed to examine the effects of an eight-week (5 min/day, 5 days/week) smartphone-based domain-generic cognitive training intervention (i.e., the smartphone game “Fruit Ninja”) on EFs in youth soccer athletes (N = 33; intervention: n = 15, passive control: n = 18; German youth soccer academy). We assessed working memory (3-back task), inhibition (Flanker & Go/NoGo task), and cognitive flexibility (number-letter task) in a pre-post design with computerized tasks. The results showed no significant time x group differences attributable to the cognitive training between the intervention group and the control group, except for a response time variable of the Go/NoGo task. These preliminary results do not suggest an application of CT as a smartphone-based game to improve EFs performance in soccer players. However, more research is needed to establish the efficacy of domain-specific interventions in high-level team sport athletes.